2023
DOI: 10.1039/d2na00839d
|View full text |Cite
|
Sign up to set email alerts
|

Organosilica nanoparticles containing sodium borocaptate (BSH) provide new prospects for boron neutron capture therapy (BNCT): efficient cellular uptake and enhanced BNCT efficacy

Abstract: Boron neutron capture therapy (BNCT), a method based on the fission of boron-10 upon neutron irradiation, has emerged as an attractive option for radiation therapy. To date, the main drugs...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…These results indicated that modifying the SP94 peptide on nanoparticles could improve the targeting ability of tumor cells and realize the enrichment of 10 B in tumor cells to improve the therapeutic effect. Exposure to neutron irradiation can lead to changes in cell structure. , Obvious changes in the cell morphology after irradiation were observed (Figure f). We calculated the ratio of the long axis to the short axis of irradiated cells using ImageJ, and we found that the result of the SP94-LB@BA-MSN group was significantly different from the other groups, which means that this group had more changes in cell morphology (Figure S8).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These results indicated that modifying the SP94 peptide on nanoparticles could improve the targeting ability of tumor cells and realize the enrichment of 10 B in tumor cells to improve the therapeutic effect. Exposure to neutron irradiation can lead to changes in cell structure. , Obvious changes in the cell morphology after irradiation were observed (Figure f). We calculated the ratio of the long axis to the short axis of irradiated cells using ImageJ, and we found that the result of the SP94-LB@BA-MSN group was significantly different from the other groups, which means that this group had more changes in cell morphology (Figure S8).…”
Section: Resultsmentioning
confidence: 98%
“…Exposure to neutron irradiation can lead to changes in cell structure. 48,49 Obvious changes in the cell morphology after irradiation were observed (Figure 3f). We calculated the ratio of the long axis to the short axis of irradiated cells using ImageJ, and we found that the result of the SP94-LB@BA-MSN group was significantly different from the other groups, which means that this group had more changes in cell morphology (Figure S8).…”
Section: 3mentioning
confidence: 99%
“…The peak around 759 cm −1 indicates the presence of the CTAB surfactant in Figure 2a [20]. The MSN framework appears at 632 cm −1 in both Figure 3a and Figure 3b [21].…”
Section: Raman Analysis Of Msn-ssmentioning
confidence: 91%
“…BPA-loaded BPMO nanoparticles significantly accumulated in tumors and BNCT mediated by BPA-loaded BPMO demonstrated a significant tumor growth inhibition. Laird et al [ 72 ] used the same strategy, but loading BSH. This study was performed in human ovarian cancer spheroids.…”
Section: Bsh Bpa Gb-10 and Boric Acid: Brief History And Optimized De...mentioning
confidence: 99%